2021
DOI: 10.1111/jne.12937
|View full text |Cite
|
Sign up to set email alerts
|

Insulin actions on hypothalamic glucose‐sensing neurones

Abstract: This aims to highlight the electrophysiological evidence supporting a critical role of insulin in regulating glucose-sensing neurones. Electrophysiological techniques have been used for over a half of a century to investigate the responses of neurones to extracellular glucose, as well as other nutrients and hormones. These techniques have evolved significantly over time, leading to a variety of different recording configurations. The distinctions between the different configurations are subtle and can be confu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 175 publications
(287 reference statements)
0
6
0
Order By: Relevance
“…Obesity impairs brain function and synapse formation by impairing insulin signaling [ 73 ]. In neurons, insulin receptor signaling-related genes, such as Irs1 and Slc2a4 , could affect the secretion of excitatory glutamate neurotransmitters [ 74 ], neuroinflammation [ 75 ], and memory formation [ 76 ]. Moreover, in neurons, synaptic formation-related genes, such as Map2 and Syp , are related to memory consolidation and synaptic plasticity [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity impairs brain function and synapse formation by impairing insulin signaling [ 73 ]. In neurons, insulin receptor signaling-related genes, such as Irs1 and Slc2a4 , could affect the secretion of excitatory glutamate neurotransmitters [ 74 ], neuroinflammation [ 75 ], and memory formation [ 76 ]. Moreover, in neurons, synaptic formation-related genes, such as Map2 and Syp , are related to memory consolidation and synaptic plasticity [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a recent review of brain insulin signaling and glucose sensing we designed a list of key genes of interest involved in either of these functions (Figure S1). 3,8,[20][21][22][23][24] Previously-published RNA sequencing data was retrieved from Okaty et al 25 with R software version 4.0.3. The dataset was directly extracted from the available Supplementary materials from Okaty et al, 25 which initially included 18 pooled fractions and 56 single neuron fractions.…”
Section: Bioinformatic Analysis Of Genes Involved In Glucose-sensing ...mentioning
confidence: 99%
“…8 VMH neurons also present the ability to detect insulin. [8][9][10] The effect of insulin in the regulation of the CRR also seems to be a key in view of studies showing that insulin regulates VMH GSNs 11 and that NIRKO mice lacking the insulin receptor in brain neurons present impaired CRR to insulin-hypoglycemia. 12 While the VMH plays an essential role in the control of the CRR in response to insulin-induced hypoglycemia, it receives projections from other brain areas which could modulate the activity of GSNs and consequently the CRR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, it has been reported that insulin resistance, lack of insulin or hypoglycemia associated automimic failure would affect glucose sensitivity of glucose-sensing neurons, thereby whole-body glucose homeostasis (see the review Ref. [ 33 ]). Obviously, the major glucoregulatory effect of insulin is to promote glucose utilization in the peripheral tissues (e.g., liver, skeletal muscle and adipose tissue).…”
Section: Central Regulation Of Glucose Homeostasismentioning
confidence: 99%